Using Ethephon for Seedhead Suppression of ‘Innovation’ Zoysiagrass - Manoj Chhetri; Jack Fry; Megan Kennelly (Kansas Agricultural Experiment Station Research Reports, 2021)
The performance of ethephon (Proxy) on seedhead suppression of ‘Innovation’ zoysiagrass was evaluated during the 2019–2020 growing season in Manhattan, KS. Treatments evaluated Proxy applied in a single autumn application at 5 fl. oz./1,000 ft2on multiple dates between August 28 and November 26, 2019. Seedhead suppression ranged from 15% (application on November 1) to 82% (applied on September 4). Dates between September 4 and October 3 were the optimum application window for ethephon application on Innovation zoysiagrass as seedhead suppression was at least 62% with minimal turf injury occurring.
Keywords: Proxy; transition zone; KSUZ 0802